The importance of practical training in specialist formation in agronomy - Kryvonos, Iryna; Кривонос, Ірина Анатоліївна; Кривонос, Ирина Анатольевна; Yeremenko, Oksana; Єременко, Оксана Анатоліївна; Еременко, Оксана Анатольевна (Варшава: Sp. z o.o. “Diamond trading tour”, 2014)
EN: During the integration process in education we can follow a tendency to increase of innovation in the sphere of training of the future specialists for agriculture production in Ukraine. The main directions of improving agricultural education articulated in the National Doctrine for the Development of Education in Ukraine, laws of Ukraine "On Education", "On Higher Education", and in a number of regulations of Education and Science of Ukraine, the Ministry of Agrarian Policy and Food of Ukraine.
Keywords: students; practical training; the learning process; skills; competence; agricultural production; студенты; практическая підготовка; учебный процесс; умения; компетентность; сельскохозяйственное производство